Laparoscopic Management of Paratubal and Paraovarian Cysts - Darwish, Atef M. (Society of Laparoendoscopic Surgeons, 2003)
OBJECTIVES: To define the proportion, methods of diagnosis, and a simplified laparoscopic technique for treating paratubal and paraovarian cysts. METHODS: We conducted a prospective cross-sectional study in the Gynecologic Endoscopy Unit of Assiut University Hospital in Assiut, Egypt in 1853 patients undergoing video-assisted laparoscopy. Transvaginal ultrasonography (TVS) was performed to detect paratubal or paraovarian cysts. Tubal shape and patency were evaluated with hysterosalpingography (HSG) in the infertile group. Diagnostic laparoscopy was performed to confirm the diagnosis of paratubal or paraovarian cysts. Small cysts were punctured and coagulated, and larger cysts required cystectomy and extraction of the cysts by using bipolar electrosurgery. Cystectomy was preceded by endocystic visualization in all cases. The primary outcomes measured included (1) correlation of the preoperative TVS, HSG, or both of these, with the laparoscopic diagnosis; (2) estimation of the success of the laparoscopic management of paratubal cysts; (3) assessment of the value of endocystic visualization prior to cystectomy; and (4) evaluation of tubal patency after laparoscopic management. RESULTS: Laparoscopically, only 118 patients (15.7%) were proved to have paratubal or paraovarian cysts. Preoperatively, TVS confirmed paratubal or paraovarian cysts in 52 (44%) patients. Cysts less than 3 cm in size (34 cases) were treated with simple puncture and bipolar coagulation of the cyst wall, whereas larger cysts (84 cases) were treated by cystectomy. Endocystic visualization using the 4-mm rigid hysteroscope was performed in 84 (71%) patients with large cysts. Statistically significant improvement occurred in tubal patency after laparoscopic management. CONCLUSIONS: Sonographic diagnosis of not uncommon paratubal and paraovarian cysts is not always feasible and requires greater awareness and accuracy. The characteristic laparoscopic differentiation of ovarian cysts is the crossing of vessels over them. Endocystic-endoscopic visualization is a simple, valuable step prior to cystectomy. Bipolar coagulation or extraction of these cysts diagnosed at laparoscopy is easy, not time-consuming, and should be routinely performed in all cases following microsurgical laparoscopic principles.